UV Irradiation of Nevi: Impact on Performance of Electrical Impedance Spectroscopy and a Convolution Neural Network - Julia K. Winkler; Holger A. Haenssle; Lorenz Uhlmann; Anissa Schweizer-Rick; Christine Fink (Mattioli1885, 2022)
Introduction: UV irradiation of nevi induces transient melanocytic activation with dermoscopic and histological changes. Objectives:We investigated whether UV irradiation of nevi may influence electrical impedance spectroscopy (EIS) or convolution neural networks (CNN). Methods: Prospective, controlled trial in 50 patients undergoing phototherapy (selective UV phototherapy (SUP), UVA1, SUP/UVA1, or PUVA). EIS (Nevisense, SciBase AB, Sweden) and CNN scores (Moleanalyzer-Pro, FotoFinder Systems, Germany) of nevi were assessed before (V1) and after UV irradiation (V2). One nevus (nevusirr) was exposed to UV light, another UV-shielded (nevusnon-irr). Results: There were no significant differences in EIS scores of nevusirr before (2.99 [2.51-3.47]) and after irradiation (3.32 [2.86-3.78]; p=0.163), which was on average 13.28 (range 4-47) days later. Similarly, UV-shielded nevusnon-irr did not show significant changes of EIS scores (V1: 2.65 [2.19-3.11]), V2: 2.92 [2.50-3.34]; p=0.094). Subgroup analysis by irradiation revealed a significant increase of EIS scores of nevusirr (V1: 2.69 [2.21-3.16], V2: 3.23 [2.72-3.73]; p=0.044) and nevusnon-irr (V1: 2.57 [2.07-3.07], V2: 3.03 [2.48-3.57]; p=0.033) for patients receiving SUP. In contrast, CNN scores of nevusirr (p=0.995) and nevusnon-irr (p=0.352) showed no significant differences before and after phototherapy. Conclusions: For the tested EIS system increased EIS scores were found in nevi exposed to SUP. In contrast, CNN results were more robust against UV exposure.